2020
DOI: 10.1101/2020.10.16.339374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphate dysregulation via the XPR1:KIDINS220 protein complex is a therapeutic vulnerability in ovarian cancer

Abstract: Clinical outcomes for patients with ovarian and uterine cancers have not improved greatly in the past twenty years. To identify ovarian and uterine cancer vulnerabilities, we analyzed genome-scale CRISPR/Cas9 loss-of-function screens across 739 human cancer cell lines. We found that many ovarian cancer cell lines overexpress the phosphate importer SLC34A2, which renders them sensitive to loss of the phosphate exporter XPR1. We extensively validated the XPR1 vulnerability in cancer cell lines and found that the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…4c). A recent study has shown a vulnerability in ovarian cancer cell lines when XPR1 activity is inhibited when Solute Carrier Family 34 Member 2 (SLC34A2) is overexpressed do to intracellular phosphate overload [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). A recent study has shown a vulnerability in ovarian cancer cell lines when XPR1 activity is inhibited when Solute Carrier Family 34 Member 2 (SLC34A2) is overexpressed do to intracellular phosphate overload [20].…”
Section: Discussionmentioning
confidence: 99%
“…4d). The most strongly linked direct neighbors of the Olaparib response profile include known oncogenes and prognostic markers of ovarian cancer, including Xenotropic And Polytropic Retrovirus Receptor 1 (XPR1) protein expression [20], Notch Receptor 3 (NOTCH3) protein expression [21], MAF BZIP Transcription Factor B (MAFB) RNA expression [22], Argininosuccinate synthetase 1 (ASS1) protein expression [23], and MEIS1 protein expression [24], among others. (Fig.…”
Section: Integrated Omics Analysis Of Olaparib Response In Ovarian Pdxmentioning
confidence: 99%